Does culture affect the relationships among utilitarian and non-utilitarian values, satisfaction and loyalty to shopping centres? Evidence from two Maghreb countries. Issue 11 (5th November 2018) - Djelassi, Souad; Godefroit-Winkel, Delphine; Diallo, Mbaye Fall
Abstract : Purpose: The purpose of this paper is to investigate the factors influencing customer loyalty to shopping centres across different emerging countries. Specifically, it seeks to determine how the cultural context moderates the direct effects of shopping centre perceived value and customer satisfaction on customer loyalty. Design/methodology/approach: A shopping centre-intercept survey was conducted among 244 consumers in Morocco and 203 consumers in Tunisia. The proposed model was analysed using partial least squares path modelling. Findings: The results demonstrate the impacts of perceived utilitarian and non-utilitarian value on customer satisfaction with a shopping centre, both moderated by the cultural context. Specifically, utilitarian, hedonic and relaxation values exert stronger influences on satisfaction in Tunisia than in Morocco; but socialisation value has a stronger impact on it in Morocco than in Tunisia. The influences of value dimensions on customer loyalty to the shopping centre do not vary between Tunisia and Morocco. Practical implications: With these results shopping centre developers and retailers can develop more efficient strategies to target Maghreb emerging countries. For example, they should focus on factors that may increase the utilitarian, hedonic and relaxation values offered by shopping centres in Tunisia but address factors that facilitate socialisation value in Morocco. Originality/value: By using a cross-culture perspective, this paper extends and enriches knowledge on shopping centre patronage in Maghreb countries. Also, it considers two non-utilitarian values (socialisation and relaxation), which are relevant in Maghreb countries.